High dose of idarubicin-based regimen for diffuse large cell AIDS-related non-Hodgkin’s lymphoma patients: a pilot study - R Gastaldi; P Martino; G Gentile; A Cafolla; I Cordone; G Giannini; C Torromeo; L Palmisano; V Picardi; M Andreotti; G Avvisati; F Mandelli (Haematologica, 2001)
BACKGROUND AND OBJECTIVES: Intensive chemotherapy (CHT) in AIDS-related non-Hodgkin’s lymphoma (AIDS-NHL patients) is a vexing problem. Our purpose was to evaluate the feasibility of a high dose idarubicin (HD-IDA)-based regimen in diffuse large cell (DLC) AIDS-NHL patients. DESIGN AND METHODS: Fourteen stage I-IV untreated DLC AIDS-NHL patients with a performance status <3 and no prior AIDS-related diseases received CIOD: cyclophosphamide, HD-IDA (25 mg/m2 in 8 patients, 20 mg/m2 in 6 patients) vincristine and dexamethasone plus granulocyte colony-stimulating factor (G-CSF) and prophylaxis against infections. The outcomes measured were: rate of response, disease-free survival (DFS), overall survival (OS) and the impact of chemotherapy on immunologic and virological parameters. RESULTS: Complete response was achieved in 13/14 cases (response rate: 93%). The median time of response and survival was 33 (range 5-79) and 35.5 (range 6-84) months, respectively. At 60 months the DFS and OS were 71% and 44%, respectively. CIOD with idarubicin 20 mg/m2 was better tolerated than that with 25 mg/m2 and was administered with a higher mean average-relative-dose-intensity (95.38+/-7% vs 83.35+/-15.59%, p=0.0001). Opportunistic infections were more frequent in patients with a baseline CD4 <100 than those with >100 cells/microL (4/5 vs 1/9: p=0.0229). After 3 CIOD courses the mean CD4 cells/microL was significantly lower (p=0.001) and the mean HIV.1 RNA load was significantly higher (p=0.045) than at baseline. INTERPRETATION AND CONCLUSIONS: The proposed chemotherapeutic regimen for AIDS-related non-Hodgkin’s lymphoma is feasible in an outpatient setting in selected patients with relatively well-preserved immune function.